The Role of Accounting Conceptual Framework in Neoliberalism - Nugraha, Farhani Kautsar; Sasongko, Ananta Wahyu; Saputri, Rizka Dibi Arryanti (Universitas Muhammadiyah Malang, 2023)
Purpose: This article discusses the relationship between accounting regulations and neoliberalism. It will also discuss changes to the conceptual framework developed by the two financial accounting standard boards, namely the IASB and FASB. Methodology/approach: This article uses a conceptual review paper methodology on accounting theories and existing research to analyzes the conceptual framework developed by the IASB and FASB. Findings: The conceptual framework developed by the IASB and FASB plays a role in the survival of neoliberalism and the financialization of the capital market Practical implications: This article presents a thorough overview of the primary concerns associated with accounting conceptual framework and contributes to the ongoing discussion on standard setting. Originality/value: This paper offers an understanding of the key aspects of the accounting conceptual framework that are closely related to neoliberalism.